SELF-MEDICATION PRACTICES AMONG UNIVERSITY STUDENTS IN GILGIT-BALTISTAN: A CASE STUDY (The Research of Medical Science Review, 2025)
Self-medication is an important public health issue around the world and is common among university students. Limited academic research is available in Pakistan in general and Gilgit-Baltistan in particular on self-medication practices among university students. This study examined the self-medication practices prevalent among university students in a mountainous university in the region of Gilgit-Baltistan, Pakistan. The study objective was to examine the prevalence of self-medication among the university students and factors that led to the self-medication practices among students in a mountainous university in Gilgit-Baltistan, Pakistan. A cross sectional survey was conducted and data was randomly collected form 181 students in the chosen university across the academic disciplines. Results show majority of the students are practicing self-medication. Major factors that led to self-medication practice are low income level, lack of access to health facilities, unavailability of health professionals, easy availability of medication, peer-influence, family environment and previous experience of self-medication. The study concludes that self-medication is prevalent among university students in Gilgit-Baltistan. Health literacy and public awareness campaigns and sensitization efforts by university and public health professionals could be effective strategies in educating the students and general public toward the adverse effects of self-medication. Future studies should take into consideration the prevalence of self-medication among the students of schools and colleges in the larger region of Gilgit and Baltistan.